Design of patch antenna using metamaterial at GSM 1800 for RF energy scavenging - Devi K.K.A.; Hau N.C.; Chakrabarty C.K.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
The paper presents a rectangular stepped patch antenna with defective ground plane using metamaterial based split ring structure for RF energy harvesting applications at downlink radio frequency range of GSM-1800. The aim of this design was to enhance the antenna performance with regards to impedance bandwidth and return loss. A simulation study of the design was carried out in the Computer Simulation Technology (CST) microwave studio. The results at the resonant frequency 1.845 GHz showed that the impedance bandwidth has increased to 596 MHz, return loss have lowest value of -27.7 dB and VSWR of 1.086. There is an improvement in performance with metamaterial based antenna. © 2014 IEEE.